2017
DOI: 10.1136/bmjopen-2017-017070
|View full text |Cite
|
Sign up to set email alerts
|

Risk of high-grade lesions after atypical glandular cells in cervical screening: a population-based cohort study

Abstract: ObjectivesTo determine how human papillomavirus (HPV) positivity of atypical glandular cells (AGCs) affects the predictive values for the presence of high-grade cervical lesions.DesignPopulation-based cohort study.SettingStockholm-Gotland region, Sweden.ParticipantsBetween 17 February 2014 and 30 June 2016, there were 562 women with AGC detected in a cervical sample. Registry linkages up to 30 June 2016 identified 392 women with an associated HPV test and a histopathological follow-up.Main outcome measurePrese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…HPV co-testing with cervical cytology has an important role in the triage of cervical squamous lesions; however, its importance is not as clear in glandular pathologies and cervical adenocancer. In a Swedish population-based study, it was reported that the HPV reflex test had a very positive predictive value in the prediction of high-grade cervical lesions in patients with AGCs, and that the planning of a follow-up schedule based on HPV status would be reasonable (13). A systematic review that analyzed the importance of HPV in AGC cytology noted that the hr-HPV test had a sensitivity of 90% in the prediction of CIN-2 and higher lesions in patients with AGC (14).…”
Section: Discussionmentioning
confidence: 99%
“…HPV co-testing with cervical cytology has an important role in the triage of cervical squamous lesions; however, its importance is not as clear in glandular pathologies and cervical adenocancer. In a Swedish population-based study, it was reported that the HPV reflex test had a very positive predictive value in the prediction of high-grade cervical lesions in patients with AGCs, and that the planning of a follow-up schedule based on HPV status would be reasonable (13). A systematic review that analyzed the importance of HPV in AGC cytology noted that the hr-HPV test had a sensitivity of 90% in the prediction of CIN-2 and higher lesions in patients with AGC (14).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 On the other hand, these abnormalities can be associated with benign conditions, such as tubal metaplasia, tubular hyperplasia or polyps. 35 One study from Ireland showed that out of 146 women referred to colposcopy following a single AGC with histologic results, 30 (20.5%) were diagnosed with CIN 2 (CIN 2, CIN 3, adenocarcinoma and cancer). 36 In our study, the CIN 2 prevalence for the women submitted to biopsy due to AGC was 12.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus was analyzed by HC2 assay (Qiagen, Gaithersburg, Maryland, EUA) for group B viruses (16,18,31,33,35,39,48,51,52, 56, 58, 59 and 68) using the residual LBC specimen, according to the instructions of the manufacturer. The viral load was determined through the quantification of light emission and expressed as a relation of the relative light unit (RLU) with the positive control (PCB), RLU/PCB.…”
Section: Hybrid Capturementioning
confidence: 99%
“…Histological examination of AGC patients revealed premalignant and malignant lesions in 26 (35.6%) patients. In the literature, this rate varies in a very wide range as 17-100% [8][9][10][11][12][13][14][15][16][17][18][19][20]23,24 . In the study of Marques JP et al 20 the average detection rate of abnormal lesion was 58% 7 .…”
Section: Discussionmentioning
confidence: 99%